(370) دور رأس المال الاجتماعي في تطوير مؤشرات التنافسية بالمحافظات / The Role of Social Capital In Developing Competitiveness Indicators In the Governorates - فريد عبد العال أحمد البقلي ، أمل زكريا وأخرون (2026)

(untitled)
يستكشف البحث دور رأس المال الاجتماعي في تعزيز التنافسية المحلية بالمحافظات المصرية، مع تطبيق على محافظة بني سويف. وأظهرت النتائج أن الثقة المجتمعية، والحوكمة الفعالة، والمشاركة المجتمعية، والتحول الرقمي تسهم في تحسين الأداء الاقتصادي وجذب الاستثمارات. كما أوصى البحث بتوظيف الذكاء الاصطناعي، وتطوير مؤشرات لقياس رأس المال الاجتماعي، وتعزيز الشفافية والشراكات المجتمعية لرفع التنافسية وتحقيق التنمية المستدامة. This research examines how social capital can enhance regional competitiveness in Egypt, using Beni Suef Governorate as a case study. The findings show that social capital, effective governance, and digital transformation improve economic performance, investment attraction, and community participation. The study recommends using artificial intelligence, strengthening governance, and promoting digital engagement to enhance local competitiveness, improve service quality, and support sustainable development across Egyptian governorates.